THE ROLE OF INTERACTIVE QUIZZES BASED ON BLOOKET IN LEARNING INTEREST IN RATIO MATERIAL FOR GRADE VII STUDENTS AT SMP NEGERI 1 SALATIGA - Roudlotul Jannah; Fitria Laiya Mahmud; Win Listyaningrum Arifin (Yayasan Amanah Nur Aman, 2026)
This study aims to analyze the role of the Blooket interactive quiz in stimulating student learning interest in Ratio material among Grade VII students at SMP Negeri 1 Salatiga, considering students’ difficulties in integrating abstract Ratio concepts with real-world problem-solving contexts. This descriptive qualitative research, employing a single case study approach, was conducted at SMP Negeri 1 Salatiga. Data were collected through triangulation (in-depth interviews, observation, and documentation) with the Math teacher and student groups. The results indicate that Blooket’s implementation is transformative in enhancing learning interest. The platform functions as (1) an Affective Catalyst, transforming formative assessment into a recreational experience that increases pleasure (88,75% of students found it engaging) and frees up cognitive resources from test anxiety. (2) a Contextual Cognitive Bridge, helping students apply Ratio concepts into strategic game scenarios (Gold Quest or Cafe Factory), bridging the gap between procedural and conceptual knowledge. (3) Conative triggers encourage active participation and significant persistence in learning. It is concluded that Blooket is an effective pedagogical innovation in stimulating all three dimensions of student learning interest simultaneously, making it highly suitable for use as a learning medium.